2009
DOI: 10.1530/eje-08-0952
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D in relation to metabolic risk factors, insulin sensitivity and adiponectin in a young Middle-Eastern population

Abstract: Objectives: Several studies suggest a link between circulating 25-hydroxyvitamin D (25(OH)D) and metabolic risk factors. However, this relation has been mainly studied in elderly and/or obese subjects. In addition, the relation between 25(OH)D and adiponectin is unclear. The purpose of this study is to look at these relations in non-obese young individuals. Design: We investigated the relation between serum 25(OH)D and adiposity, blood pressure, glucose metabolism, lipid profile, and adiponectin in 381 randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
138
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(151 citation statements)
references
References 39 publications
10
138
3
Order By: Relevance
“…In the present study, participants with MetS had significantly lower 25(OH)D levels than participants without MetS. The inverse relationship between serum 25(OH)D and FBG was reported in other studies, too (20,21,26,28,60) . However, in a study by Ashraf et al on obese African-American adolescent females, no relationship was found between serum 25(OH)D and FBG (23) .…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, participants with MetS had significantly lower 25(OH)D levels than participants without MetS. The inverse relationship between serum 25(OH)D and FBG was reported in other studies, too (20,21,26,28,60) . However, in a study by Ashraf et al on obese African-American adolescent females, no relationship was found between serum 25(OH)D and FBG (23) .…”
Section: Discussionsupporting
confidence: 82%
“…However, in both the studies subjects with high serum 25(OH)D concentrations tended to have higher HDL-C concentrations than those with lower serum 25(OH)D concentrations. Conversely, in a study on 201 men and 180 women, Gannagé-Yared et al (2009) found no significant association between serum 25(OH)D and TAG, whereas in men there was a significant negative relation with serum LDL-C. A negative relation between serum 25(OH)D and both TC and LDL-C was also reported by Chiu et al (2004) in a study on 126 subjects, whereas in that study no association between serum 25(OH)D and TAG was found. And finally, no significant association between fasting serum lipids and serum 25(OH)D was found in 524 subjects in the MRC-Ely study (Forouhi et al, 2008).…”
Section: Discussionmentioning
confidence: 76%
“…However, the relation between serum 25(OH)D and serum lipids, which are among the major risk factors for cardiovascular disease (Kannel et al, 1971), is more uncertain (Ford et al, 2005;John et al, 2005;Martins et al, 2007;Forouhi et al, 2008;Hyppönen et al, 2008;Gannagé-Yared et al, 2009;Lee et al, 2009). We have therefore examined the cross-sectional relation between serum 25(OH)D and serum lipids in 12 000 subjects from the Tromsø study, and also examined the longitudinal relation between change in serum 25(OH)D concentrations and change in serum lipids over a 14 years period.…”
Section: Introductionmentioning
confidence: 99%
“…Parathyroid hormone (PTH), which increases in the presence of vitamin D insufficiency, was also linked to serum lipids (9) . However, the results are inconsistent and associations often vanished after controlling for confounding variables (5,6,8) .The question arises whether the assumed associations between serum lipids and vitamin D and PTH are independent from other cardiovascular risk factors like obesity, which has been associated with elevated serum lipids (10) and may also interfere with the vitamin D endocrine system (11) . In addition, the associations may differ by sex considering the differences in body composition and serum lipid levels between women and men.…”
mentioning
confidence: 99%
“…In addition, the associations may differ by sex considering the differences in body composition and serum lipid levels between women and men. Previous studies were mostly performed on ambulatory patients and/or vitamin Ddeficient, middle-aged or overweight and obese individuals and often without adjustments for potential confounders, such as the association between vitamin D and PTH, body composition, medical conditions and/or lifestyle factors, including sun exposure, physical activity and habitual diet (4)(5)(6)(7)9,(12)(13)(14)(15) .…”
mentioning
confidence: 99%